THE INFLUENCE OF COMPETENCY, AUDITOR ETHICS, AND INDEPEND-ENCE ON AUDIT QUALITY - Kamil, Islamiah; Ariani, Meiliyah; Irawan , Indra Ade (Moestopo International Review on Social, Humanities, and Sciences, 2023)
The concept of accounting and corporate financial reporting is an important aspect that has also been widely recognized by various parties, including the government, investors, creditors, and the public. The existence of the public accounting profession that was born and raised from the demands of the community to have an independent and competent accountant in examining the financial statements of a company. This study aims to determine the influence of auditor competence, ethics and independence on audit quality. The data used in this study is primary data in the form of questionnaires filled out by auditors working at Public Accounting Firms in the West Jakarta and South Tangerang areas. The population of this study is auditors working at Pub-lic Accounting Firms in West Jakarta & South Tangerang. The sample in this study was 100 respondents. Sampling using non-probability sampling method, namely convenience sampling and using multiple linear regression analysis using SPSS21. The results showed that competence had a significant effect on audit quali-ty, auditor ethics had a significant effect on audit quality and independence did not have a significant effect on audit quality.